MEMERDEKAKAN PEMBELAJAR DI TENGAH TERGERUSNYA ROH PENDIDIKAN - Mustafa Hizkia Simatupang (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2020)
Abstract: Public expectations for improvement of the National Curriculum rise up again, while a positive response to the appointment of the Minister of Education and Culture from the millennial generation. Fundamental improvements in the educational system appear to be more in line with the demands of the works and the current development. The liberating education is closely related to the strategy of liberated learning. Community resistance related to new policies in primary and secondary education as well as high education is regarded as a reasonable reaction as the changes constantly intersect with the unaccommodated interests of certain groups. However, regulatory breakthroughs are vital to the effort of leapfrogging progress. In order to promote national education, it must be accompanied by an increase in teacher competency. It requires some considerations such as, a) the quality of students; b) whether it is concise, measurable and expandable; c) evidence-based and research results; d) refers to the role of teachers and e) whether it is adaptive to the current development. Offsetting the development of digital science and technology in this third millennial era, the teacher’s competence model must also be flexible to the changes. The categories that need to get a touch of the teacher’s competency model include: 1) Professional Knowledge Mastery; 2) Professional Learning Practices, and 3) Sustainable Professional Development. Teacher Professional Education Program (PPG) is able to increase the professionalism of teachers. Improving teacher’s competence and quality training is able to cause to emerge or refine the motivation and passion of teachership. Regular and programmed training and continuous monitoring/evaluation will liberate the teacher and encourage students to reason that is the spirit of liberating education.Keywords:  Liberating, Liberated Learning, The Spirit of Education, Professional Teacher, Students.